Understanding gender differences in availability, accessibility and use of climate information among smallholder farmers in Malawi. (3rd July 2021) - Henriksson, Rebecka; Vincent, Katharine; Archer, Emma; Jewitt, Graham
ABSTRACT: Smallholder farmers in the sub-Saharan Africa are vulnerable to climate variability and change, and are thus in need of adaptation. Access to climate information, such as weather forecasts, has been identified as a potential enabler for improved adaptation, but such access tends to be strongly gendered. This study uses qualitative and quantitative data to assess the availability, accessibility and use of climate information among smallholder sugarcane farmers in southern Malawi, disaggregating data according to gender, age, education level and landholding size. We found that radio is the most common, and preferred, means of accessing forecasts for men and women, but that women farmers also prefer to access forecasts through a knowledge broker. Those farmers with higher levels of education (mostly men) prefer to also obtain forecasts via internet and cell phone. Most farmers consider the forecasts reliable, timely and understandable – more so in the case of men than women. Understanding gendered preferences and barriers to climate information access is crucial for benefits of adaptation to be accessed equitably.